2005
DOI: 10.1634/stemcells.2004-0066
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hematopoietic Stem Cell Functioning After Serial Transplantation and During Normal Aging

Abstract: Adult somatic stem cells possess extensive self-renewal capacity, as their primary role is to replenish aged and functionally impaired tissues. We have previously shown that the stem cell pool in short-lived DBA/2 (D2) mice is reduced during aging, in contrast to longlived C57BL/6 (B6) mice. This suggests the existence of a genetically determined mitotic clock operating in stem cells, which possibly limits organismal aging. In the study reported here, unfractionated bone marrow (BM) cells or highly purified Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 53 publications
9
93
1
Order By: Relevance
“…Poor engraftment with older donors has also been shown in murine transplant models, 5,6 and this kind of "aging" in grafts from older donors may be related to ageassociated modifications in DNA methylation patterns 29 and/or shorter length of telomeres in hematopoietic stem or progenitor cells from older donors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Poor engraftment with older donors has also been shown in murine transplant models, 5,6 and this kind of "aging" in grafts from older donors may be related to ageassociated modifications in DNA methylation patterns 29 and/or shorter length of telomeres in hematopoietic stem or progenitor cells from older donors.…”
Section: Discussionmentioning
confidence: 97%
“…[2][3][4] In addition to these, biological speculation from previous published studies regarding hematopoietic stem cell repopulation and donor-derived T-cell function have suggested that transplantation from older donors may result in a higher incidence of engraftment failure and acute GvHD (aGvHD), and, as a result, increase transplant-related death and lead to inferior OS. According to murine studies, hematopoietic stem cells from older donors do not re-populate as efficiently, 5,6 and grafts from older donors have a higher ratio of memory T cells to naïve T cells; 7 an increase in peripheral blood memory T cells has been shown to be related to the occurrence of aGvHD in humans. 8,9 The influence of donor age in unrelated hematopoietic cell transplantation has long been discussed in various studies, and some have shown a relationship between older donor and worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…HSCs isolated from older mice show defects in mobilization and homing to bone marrow (Morrison et al, 1996;Kim et al, 2003;Liang et al, 2005;Xing et al, 2006). In competitive transplantation assays, a rigorous test for both self-renewal and multipotency during which donor HSCs are co-injected with wild-type bone marrow and assessed for their ability to regenerate all blood lineages, aged HSCs shows defect in long-term reconstitution of the immune system (Sudo et al, 2000;Kamminga et al, 2005;Rossi et al, 2005;Chambers et al, 2007). Aged HSCs also give rise to more cells of myeloid lineage at the expense of lymphoid fates (Sudo et al, 2000;Kim et al, 2003;Rossi et al, 2005;Cho et al, 2008;Guerrettaz et al, 2008).…”
Section: Defects In Number In Aging Stem Cellsmentioning
confidence: 99%
“…Serial transplantation was performed as described 17 using CD45.1 recipients receiving 5¥10 6 BM cells from either control or estradiol treated mice. Four months posttransplantation, recipients were analyzed and 5¥10 6 BM cells were transplanted into secondary or third recipients.…”
Section: Serial Transplantationmentioning
confidence: 99%